Perancangan dan Pengembangan Website Tracer Study di SMA Katolik Yos Sudarso Batam - Syaeful Anas Aklani, S.Kom., M.Kom.; Delvin Jason; Dr. Hendi Sama, S.Kom., M.M.e-Business. (National Conference for Community Service Project (NaCosPro), 2025)
This study examines the design and development of a Tracer Study website at SMA Katolik Yos Sudarso Batam to address the issue of fragmented and non-integrated alumni data. The implementation began with structured interviews of administrative staff to identify functional requirements, followed by UI/UX design in Figma with iterative partner feedback, and development using PHP Laravel and a MySQL database. The system features alumni registration with NIS validation, an analytics dashboard for administrators, and a bulk data import module. Results indicate a shift from manual to automated data verification, easier monitoring of alumni progression, and comprehensive technical documentation and user guides. Recommendations for future research include implementing automated notification mechanisms, conducting regular performance and security audits, and extending analytical modules to support more responsive curriculum decision-making.